Effects of species and sex on the gut microbiome of four laboratory-reared fruit fly lines (Diptera: Tephritidae) using full-length 16S rRNA PacBio Kinnex sequencing - Sayaka Aoki; Mikinley Weaver; Tyler J. Simmonds; Ikkei Shikano; Scott M. Geib; Charles J. Mason (BMC Microbiology)
Abstract Background Insect gut microbiomes, including tephritid fruit flies, are shaped by multiple endogenous and environmental factors. While host species is a well-known driver of the gut microbiome of adult tephritids, the influence of sex is less clear. Our study evaluated the impacts of host sex and species influence the microbiome in laboratory-reared tephritids when controlled for location, time, and adult diet. We evaluated the gut microbiome of four lines of pest tephritid fruit fly adults (Bactrocera dorsalis, Bactrocera latifrons, Ceratitis capitata, Zeugodacus cucurbitae) using near full-length 16S rRNA sequencing with a PacBio Kinnex concatenation-based approach. We analyzed groups of males and females from each species at the same set of time, across four timepoints in a core insectary. Results Results demonstrate a clear impact of fruit fly species on the gut microbiome composition of the different fruit flies. Furthermore, for B. dorsalis, B. latifrons, and C. capitata, we saw an influence of sex on ASV composition. However, while there was a separation of samples between the sexes for each timepoint, there was no characteristic male or female microbiome in all cases. The use of near full-length 16S rRNA sequencing did not have a marked improvement in beta-diversity interpretation over V4 subunit, with most detected taxa matching those described from other tephritids, but did allow for improved taxonomic classification at the genus level. Conclusions Our results demonstrate that under laboratory conditions, different fruit fly species still exhibit distinct microbiomes. The impact of sex did have an impact on the gut microbiome of some species, but the magnitude of effect differed between hosts. This indicates that the sex has some impact on structuring the gut microbiome, but in a case-by-case basis. While full-length 16S rRNA sequencing affords improved classification, our study did not indicate an improvement over partial-fragments on beta-diversity metrics.